The evaluation of flat plate solar cooker / Fatimah Mohamed - Mohamed, Fatimah (2006)
In Malaysia, the utilization of solar energy is still in early stage. The development and utilization of solar energy at our country is not rapid as other country. At present, Malaysia have developed only several devices that used solar energy such as solar water heating system, flat plate solar collector and solar panel. However, at this moment our country still does not have developed any types of solar cooker. Therefore, in order to know whether solar cooker can be performed well in this country, it is decided to conduct a research on flat plate solar cooker. The main objective of this research is to design and construct a simple flat plate solar cooker and also to evaluate and compare the effectiveness of the cooker using copper and aluminum plate. From the result, it has shown that the performance of solar cooker for copper type is better than the aluminum type. Copper type achieves higher temperature than aluminum type where the maximum temperature of copper is 100°C and for aluminum is 91°C. The copper type is more effective than the aluminum type because the thermal conductivity of the copper is higher than aluminum.